The Role of Mentoring (Mental Guidance) Activities in Improving the Quality of Islamic Religious Education for Class XI Students at SMK Negeri 3 Metro Lampung - Septiawan, Andi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study aims to investigate the role of mentoring (mental guidance) activities in enhancing the quality of Islamic religious education for Class XI students at SMK Negeri 3 Metro Lampung. Mentoring activities in this context refer to structured guidance sessions provided by teachers or mentors that aim to support students in their religious and moral development. These activities are designed to integrate cognitive, affective, and psychomotor aspects of education to create a holistic learning experience. The research utilizes a qualitative approach with descriptive methods to detail the real-life implementation and impact of these mentoring activities. Data was collected through observations, interviews with students, teachers, and mentors, as well as relevant documentation. The findings indicate that mentoring activities significantly contribute to the development of students' religious attitudes and behaviors. Students participating in mentoring sessions showed improvements in their understanding of Islamic teachings, their application of moral values in daily life, and their engagement in religious practices such as prayers and Quran recitation. This research highlights the importance of consistent and well-structured mentoring programs in schools. Such programs can complement the formal curriculum and provide students with the necessary support to enhance their religious education and moral character. The study concludes that the integration of mentoring activities within the school curriculum at SMK Negeri 3 Metro Lampung has positively impacted the quality of Islamic religious education for Class XI students.Mentoring,